ENHANCING EFL STUDENTSâ WILLINGNESS TO COMMUNICATE: TEACHERSâ BELIEFS ABOUT THEIR ROLES AND STRATEGIES - Sari, Funny Amalia (Kajian Linguistik dan Sastra, 2016)
This study aims to investigate teachersâ beliefs about the scope of theirÂ roles in terms of interaction strategies in order to develop and maintain theirÂ learnersâ willingness to communicate (WTC). Four experienced teachers of twoEnglish courses in Indonesia were asked to answer an open self-completionÂ questionnaire that was designed based on the three interaction strategies proposedby Lee and Ng (2010). The study suggests any pedagogic interventionsÂ always depend on good teaching: one method alone does not promise success.Â This present study is expected to contribute to the comprehension of teachersâÂ influence to learnersâ WTC particularly to language teacher development.